Self-help: a systematic review of the efficacy of mental health apps for low-and middle-income communities - Gama, Beauty (My University, 2021)
Background: Low and middle-income countries are faced with the challenges of providing adequate and accessible mental health care. This, however, has been a slow process due to the unavailability of resources. With the shift towards a more technologically reliant society, mental health apps offer the opportunity to provide mental health care that is accessible at any geographical and economic location. Aim: The study aims to determine the efficacy of mental health apps in low and middle-income communities (LMICs) using a systematic review. Methods: The study utilises a systematic review following the PRISMA guidelines. Articles published within the last 5 years (2015-2020) were eligible for inclusion in the study. This yielded six articles (qualitative, quantitative, and mixed methods) that met the inclusion criteria that were analysed using content analysis and thematic synthesis. Results: The development of themes followed a deductive approach guided by the Availability Accessibility Acceptability Quality framework (AAAQ) with regards to the provision of adequate service delivery. The results speak to the current available mental health care system in LMICs, some of the barriers to accessing mental health care and how mental health apps offer a way to bridge that in LMICs, the implementation of mental health apps, and the considerations they have to the communities that they are used in and lastly, the quality of care that mental health apps could potentially provide in LMIC contexts. Conclusion: The study offers valuable insight towards mediating some of the struggles faced in the implementation of appropriate mental health care in LMICs using mental health apps. A recommendation is for the expansion of similar studies in other contexts will assist in developing appropriate and accessible mental health care
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts (in Social and Psychological Research) in the Department of Psychology, School of Human and Community Development, Faculty of Humanities, at the University of the Witwatersrand, Johannesburg, 2021